Five lines of code : how and when to refactor - Clausen, Christian (Manning Publications, 2021)
Down to earth, focused, and right on point. It will challenge you without intimidating you and without insulting your intelligence. Robert C. Martin In Five Lines of Code you will learn: The signs of bad code Improving code safely, even when you don't understand it Balancing optimization and code generality Proper compiler practices The Extract method, Introducing Strategy pattern, and many other refactoring patterns Writing stable code that enables change-by-addition Writing code that needs no comments Real-world practices for great refactoring Improving existing code--refactoring--is one of the most common tasks you'll face as a programmer. Five Lines of Code teaches you clear and actionable refactoring rules that you can apply without relying on intuitive judgements such as "code smells." Following the author's expert perspective--that refactoring and code smells can be learned by following a concrete set of principles--you'll learn when to refactor your code, what patterns to apply to what problem, and the code characteristics that indicate it's time for a rework. about the technology Every codebase includes mistakes and inefficiencies that you need to find and fix. Refactor the right way, and your code becomes elegant, easy to read, and easy to maintain. In this book, you'll learn a unique approach to refactoring that implements any method in five lines or fewer. You'll also discover a secret most senior devs know: sometimes it's quicker to hammer out code and fix it later! about the book Five Lines of Code is a fresh look at refactoring for developers of all skill levels. In it, you'll master author Christian Clausen's innovative approach, learning concrete rules to get any method down to five lines--or less! You'll learn when to refactor, specific refactoring patterns that apply to most common problems, and characteristics of code that should be deleted altogether. about the audience For developers of all skill levels. Examples use easy-to-read Typescript, in the same style as Java and C#. about the author Christian Clausen works as a Technical Agile Coach, teaching teams how to refactor code. A delightful and fun introduction to one of the most overlooked parts of programming--refactoring. Charles Lam, EVN AG Gave me new insights on how to keep my code readable and maintainable. I highly recommend it. John Norcott, Webstaurantstore These techniques are simple but powerful, and the exercises makes it easy to learn them. They can be used in any language I know!